Selective Information Acquisition in Disaster Scenarios: A Study on Health Information Behavior in Aceh - Koto, Marini; Rosemary, Rizanna; Rahman, Alfi; Muharman, Nadia; Nisa, Uswatun (TDMRC, Universitas Syiah Kuala, 2024)
Aceh, a province recognized for its high disaster risk potential, is frequently subjected to various natural calamities. The inhabitants of this region often face anxiety, uncertainty, and an overload of information during such events, necessitating a selective approach to information acquisition. This study explores this phenomenon, specifically the selective acquisition of health information amid disaster scenarios. The focus is on understanding how individuals prioritize information that they perceive as relevant and valuable, while disregarding what is deemed unimportant or unreliable. Addressing a notable gap in existing literature on health communication during disasters, this research emphasizes its critical role in enhancing disaster preparedness. Data were collected through Focus Group Discussions (FGD) involving 30 participants across three hazard-prone areas in Aceh: Central Aceh (landslides), North Aceh (floods), and West Aceh (earthquakes). Findings reveal that participants typically engage in passive information seeking, selectively assimilating health information that conforms to their pre-established subjective beliefs, values, and emotional states from trusted sources. The study offers insights into how individuals manage health information in crisis situations and suggests that stakeholders in disaster management devise targeted communication strategies to effectively disseminate vital health information during disasters.